Tác động của đòn bẩy đến quản trị lợi nhuận dựa trên khoản dồn tích: Trường hợp của các công ty niêm yết tại Việt Nam - Trần Thị Hồng, Diễm (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2021)
The primary aim of this study is to examine the impact of leverage on accrual-based earnings management practices for companies listed on the Vietnamese stock exchange. In addition, study objects for firms that undergo leverage increases and highly leveraged firms and in doing so, provides support for the notion that leverage changes and leverage levels have differing impacts on earnings management. A sample of 131 companies listed on the Vietnamese stock exchange during the period 2017–2019 forming into 393 observations. Using panel data and feasible generalised least square (FGLS) regression models to empirically analyze the effect of firm leverage on earnings management. The empirical results show that increased leverage, relative to consistently high levels of leverage, is associated with negative accruals, suggesting reduced earnings management, accrual-based earnings management. In addition, the empirical results show that Return on Assets (ROA), Interest Expense (INTEXP) are associated with positive accruals; the Self-Financing Ratio (SFR), cash flow from operation (CFO) are associated with negative accruals.